Identification of altered microRNA target genes and pathways in cervical intraepithelial neoplasia (Research, Society and Development, 2022)
MicroRNAs are single-stranded, non-protein-coding RNA molecules of about 18-25 nucleotides, which are capable of regulating expression at the post-transcriptional level. Its dysregulation has been widely studied in cancer, but little has been documented in pre-malignant lesions, such as Cervical Intraepithelial Neoplasms (CIN). In this context, this study aims to search the literature for microRNAs associated with NICs, as well as perform in silico prediction, in order to know the main genes and pathways that are regulated by them. For this, a search was carried out in the literature regarding the association of microRNAs in pre-neoplastic lesions in cervical cancer. The research was carried out in databases such as Pubmed and Science Direct, and scientific articles with publication date between the years 2010 to 2021 were selected and analyzed. , through bioinformatics tools. According to the inclusion and non-inclusion selection criteria, 8 articles were included in the literature review, which totaled 22 deregulated microRNAs in cervical intraepithelial lesions, with 18 microRNAs in high-grade lesions and 4 microRNAs in low-grade lesions. In silico analysis revealed that these microRNAs regulate genes such as: FZD7, ESR1 and BRAF, which are involved in major carcinogenesis pathways, such as the proteoglycan and stem cell pathway. The data presented demonstrate the deregulation of these biomolecules in pre-malignant cervical cancer samples.